1999
DOI: 10.1073/pnas.96.14.8271
|View full text |Cite
|
Sign up to set email alerts
|

The alternative oxidase lowers mitochondrial reactive oxygen production in plant cells

Abstract: Besides the cytochrome c pathway, plant mitochondria have an alternative respiratory pathway that is comprised of a single homodimeric protein, alternative oxidase (AOX). Transgenic cultured tobacco cells with altered levels of AOX were used to test the hypothesis that the alternative pathway in plant mitochondria functions as a mechanism to decrease the formation of reactive oxygen species (ROS) produced during respiratory electron transport. Using the ROS-sensitive probe 2,7-dichlorof luorescein diacetate, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
730
4
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,007 publications
(769 citation statements)
references
References 50 publications
27
730
4
8
Order By: Relevance
“…The ferroxidase center in mitochondrial ferritin contains a diiron carboxylate center (Levi et al 2001). A related site is present in the alternative oxidase (AOX) found in the mitochondrial respiratory chain of plants and some fungi (Maxwell et al 1999).…”
Section: Metal Ions Usage Within Mitochondriamentioning
confidence: 99%
“…The ferroxidase center in mitochondrial ferritin contains a diiron carboxylate center (Levi et al 2001). A related site is present in the alternative oxidase (AOX) found in the mitochondrial respiratory chain of plants and some fungi (Maxwell et al 1999).…”
Section: Metal Ions Usage Within Mitochondriamentioning
confidence: 99%
“…In particular, Maxwell et al (1999) demonstrated the engagement of this mechanism as a response to the formation of reactive oxygen species that resulted in oxidative stress. They suggested that the role of AOX was to decrease this stress.…”
Section: Evaluation Of the Significance Of O 2 Uptake Mechanisms-mentioning
confidence: 99%
“…Intracellular production of ROS was measured using 2 0 ,7 0 -dichlorofluorescein diacetate (H 2 DCF-DA) (Maxwell et al 1999). Dichlorofluorescein (DCF) fluorescence was measured using a microplate spectrofluorometer (Molecular Devices Spectra Max Gemini).…”
Section: Measurement Of Rosmentioning
confidence: 99%
“…Excessive mitochondrial ROS formation is seen as an indicator of mitochondrial dysfunction (Raha and Robinson 2000) and is a key trigger of programmed cell death (Lam et al 2001). Using transgenic tobacco cells, Maxwell et al (1999) showed that cells lacking AOX had increased mitochondrial-derived ROS formation and an upregulation of key genes involved in antioxidant defence, when compared with wild-type cells. More recently, these same AOX antisense cells have been shown to have a greater susceptibility for mitochondrial-dependent and mitochondrial-independent cell death .…”
Section: Introductionmentioning
confidence: 99%